The Impact of Gender Discrimination on Women’s Access to Education in Aworanga Village Putuda Parish Gulu City Northern Uganda - Winifred Aromorach (Uganda Christian University, 2024)
Gender discrimination is so far a wide spread problem of disparity affecting many regions worldwide and its particularity in rural areas. This issue is pervasive in northern Uganda which experienced LRA wars and their villages were affected. Therefore this research is conducted in Aworanga village, Patuda parish in Gulu City which has a record of post conflict and gender discrimination in girls’ access to education. This research study is to create awareness among the people of Aworanga village about the negative effects of gender discrimination and awaken them to the growing world where equality is for all but not dictated by culture and their collective efforts will help achieve such. The study used Quantitative and qualitative methods to collect data so as to find out the different disparities in primary school enrollment rates of girls compared to boys, and disparities like cultural social norms, preference for educating boys with the limited resources due to economic constraints, limited school facility, girl child labor to contribute in the family income, safety concerns and limited school facilities for girls were noted as from the results of questionnaires filled by 35 respondents. These affected girls’ access to education and so resulted to high dropout rates, low enrollment and academic performance of girls, low class attendance, loss of self-esteems and confidence, trauma caused by sexual harassment and conflicts, early marriages and pregnancies and hence low employment in the job market because of low education attainment level. However, various strategies have been concluded that policies on human rights should be reformed, stricter laws enforced against abusers, encourage community engagement and participation and provision of scholarship and financial help by the government through partnership with NGOs who can create awareness and advocate for girl child equal education to combat primitive cultural beliefs and practices, this will reduce gender discrimination on women’s access to education.